If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(x + -7) = 0 Reorder the terms: 12(-7 + x) = 0 (-7 * 12 + x * 12) = 0 (-84 + 12x) = 0 Solving -84 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '84' to each side of the equation. -84 + 84 + 12x = 0 + 84 Combine like terms: -84 + 84 = 0 0 + 12x = 0 + 84 12x = 0 + 84 Combine like terms: 0 + 84 = 84 12x = 84 Divide each side by '12'. x = 7 Simplifying x = 7
| 1.07(4x+10)+5.30=1.08(4x+5)+8.60 | | 1+0.07(4x+10)+5.30=1+0.08(4x+5)+8.60 | | 229/4=57.25 | | 7v+3+3v+4= | | 6x-(3x-4)=9x+22 | | x/3-13=12 | | 1+0.07(4x+10+5.30)=1+0.08(4x+5+8.60) | | 1/0.19=12/n | | -6+6x=-36+9x | | 3(r-6)=2(r+4) | | x^2+11=4x | | 23+8=j | | -1=(x+1) | | -12x-208=56-x | | w/6-2=5 | | 1/2x160 | | 1/4x160 | | -38-x=-2+5(-3x+4) | | 7+x/=9 | | 4z-z+vz+1+1+2z= | | 17=n-8 | | -8/6x=24 | | (9Z+4)/5-8=5.4 | | y-28= | | x+10=-10+6x | | (-2+i)(-2-i)= | | 5(x+y)=20+3y | | 24=-5x+6 | | 15+g=65 | | 5+4(x-1)=2x-9 | | 16/7=9/b | | -126-12x=50-4x |